Muzara'ah, Musaqoh And Mugharasah Contracts In Fiqh Muamalah - Mustika Lestrai Ramadani; Siti Kholis Napsiah; Muhammad Nur Iqbal (Jurnal Multidisiplin Sahombu, 2025)
This journal aims to provide a comprehensive overview of partnership contracts in business. There are 3 partnership contracts that will be discussed in this journal, namely Muzara'ah, Musaqoh and Mugharasah . Data were obtained through library research . Data analysis was carried out qualitatively on all literature sources. With objective and reliable data analysis, it is expected that accurate and valid discussions will be obtained as answers to all problem formulations that have been made in this study. The data processing method explains the data processing and analysis procedures in accordance with the approach taken. This study uses a data processing method carried out by describing the data in the form of regular, sequential, logical, non-overlapping, and effective sentences so as to facilitate understanding and interpretation of the data. The musaqah contract and the muzara'ah contract are made into one, if the contract is separate, the contract is invalid (void). Hanafiah scholars say that the handover of empty land to farmers for a certain period of time to be planted with trees with the provision that the land and trees growing on it belong to both the landowner and the farmer, the law is not allowed.